Analisis Pencapaian Target Produksi Kertas untuk Peningkatan Efisiensi Produksi di PT OKI Pulp and Paper di Sungai Baung Ogan Komering Ilir - Alwi Alwi (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The accomplishment of operational targets is what is generally anticipated by each company. Since the accomplishment of targets can uphold the company magnificent exhibition. In this manner, the conversation isn't accomplished so it is important to figure out what components influence it. In accomplishing organization focuses on, a cycle identified with the objectives to be acquired is required. To accomplish greatest and successful outcomes, it is important to have a satisfactory inside control structure, which upholds the organization's operational advances with the goal that it moves along as expected and is coordinated and powerful. Examination directed at PT. OKI Pulp and Paper, situated on the Sungai Baung, is to figure out how to accomplish paper focuses for expanded proficiency underway. In light of the consequences of the examination it very well may be presumed that the execution of target assessment for expanding paper effectiveness at PT. OKI Pulp and Paper are sufficient, this is seen from the information got identified with guideline, data and correspondence, brief control and checking exercises as far as effectiveness.